Androgen receptor levels during progression of prostate cancer in the transgenic adenocarcinoma of mouse prostate model (Medical Journal of Indonesia, 2010)
Aim To construct tissue microarrays (TMAs) that consisted of prostate tumours from the transgenic adenocarcinoma of mouse prostate (TRAMP) mice and non-transgenic murine prostates and to assess androgen receptor (AR) levels during progression of prostate cancer in TRAMP mice by immunohistochemistry.Methods Haematoxylin and eosin (H&E) sections from the ventral and dorso-lateral prostate lobes of non-transgenic, intact TRAMP and castrated TRAMP were used to demarcate regions of interest for TMAs construction. The samples on TMAs were used to evaluate AR expression using video image analysis (VIA).Results AR was expressed during cancer progression, but AR levels were reduced or absent in late stage disease. Furthermore, when AR levels were compared in tumours from intact and castrate animals, a significant increase in AR levels was observed following androgen ablation.Conclusion Similar to clinical prostate cancer, in the TRAMP model, prostate tumours evolve mechanisms to maintain AR expression and AR responsive gene pathways following castration to facilitate continued tumour growth. (Med J Indones 2010; 19:5-13)Keywords : androgen ablation therapy, tissue microarrays, haematoxylin and eosin, video image analysis